How to implement the European digital single market: identifying the catalyst for digital transformation. Issue 1 (2nd January 2022) - Schmidt, Carsten; Krimmer, Robert
ABSTRACT: COVID-19 is regarded as a major driver for digital transformation of our society and potentially as a boost for further digital single market integration. From the current perspective, pandemics cannot be avoided, but fully enabled digital societies will be better prepared to cope with them in future. This will, however, require reliable digital infrastructures to be put in place and further developed. Member States of the European Union and the European Commission have worked for more than 30 years to realise a European Digital Single Market. One key element in this development has been the so-called 'Large-Scale Piloting' (LSP) approach. This paper will focus on implementation of the 'Once-Only Principle' Pilot (TOOP) as part of LSP and the adjoint Single Digital Gateway Regulation (SDGR). This paper will examine whether, and how these initiatives can foster further integration into a digital single market.